Recursos de información como mediadores en los procesos de educación inicial: propuesta macro para instituciones públicas de Ecuador - Parreño Vera, Monica Alexandra; Arévalo Anchundia, Karina Miosotty; Saeteros López, Mónica Bibiana (Scripta Mundi, 2026)
Equitable access to information resources is an essential component in knowledge building and strengthening educational processes from early childhood, as these materials mediate between the child's experience and their sociocultural environment. In the Ecuadorian context, public institutions face limitations in the availability, relevance, and updating of these resources, which affects the quality of pedagogical processes and the early development of information literacy skills. Based on this, the objective of this study is to design a framework proposal for Ecuadorian public institutions to create information resources for early childhood education. The research employs a qualitative approach with a descriptive scope and emphasizes the use of content analysis to examine official reports, scientific articles, and educational policies related to the use of informational materials in early childhood. The results demonstrate the need to integrate information resources with national curricula, promoting their design based on criteria of accessibility, cultural relevance, and institutional sustainability. Meanwhile, a comprehensive information resources policy can significantly contribute to strengthening meaningful learning and cognitive development in early childhood education. Furthermore, it is confirmed that cooperation among teachers, librarians, and educational policymakers is essential to ensure that the materials created meet the real needs of the Ecuadorian educational context and foster an inclusive and transformative information culture.
Keywords: Information resources; Early childhood education; Meaningful learning; Educational policies